2010
DOI: 10.1038/onc.2010.70
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of EGFR pathway signaling and the metastatic potential of breast cancer cells by PA-MSHA mediated by type 1 fimbriae via a mannose-dependent manner

Abstract: To identify more therapeutic targets and clarify the detailed mechanisms of Pseudomonas aeruginosa-mannosesensitive hemagglutinin (PA-MSHA) on breast cancer cells both in vitro and in vivo. PA-MSHA was administered to epidermal growth factor receptor (EGFR)-positive human breast cancer cell lines MDA-MB-231HM and MDA-MB-468 in vitro and to mice bearing tumor xenografts. The mannose cocultured test was used to detect the effect of mannose on PA-MSHA-induced cell proliferation, cell cycle arrest, apoptosis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 31 publications
6
32
1
Order By: Relevance
“…EGFR activation promotes disruption of adherens junctions through induction of MMP-9 (8). Our previous study showed that Pseudomonas aeruginosa mannose-sensitive hemagglutinin (PA-MSHA) could significantly inhibit protein levels of EGFR, p-ERK, p-AKT, VEGF, and MMP-9, while also inhibiting the metastatic potential of breast cancer cells by inhibition of the EGFR signaling pathway (22). In this study, we again found that TIEG1 could inhibit protein levels of EGFR, p-ERK, p-AKT, VEGF, and MMP-9.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…EGFR activation promotes disruption of adherens junctions through induction of MMP-9 (8). Our previous study showed that Pseudomonas aeruginosa mannose-sensitive hemagglutinin (PA-MSHA) could significantly inhibit protein levels of EGFR, p-ERK, p-AKT, VEGF, and MMP-9, while also inhibiting the metastatic potential of breast cancer cells by inhibition of the EGFR signaling pathway (22). In this study, we again found that TIEG1 could inhibit protein levels of EGFR, p-ERK, p-AKT, VEGF, and MMP-9.…”
Section: Discussionsupporting
confidence: 61%
“…Breast cancer patients with tumors positive for EGFR expression have a less favorable prognosis than those with tumors negative for EGFR expression. However, for those patients whose tumors have been tested and found to be EGFR positive, blocking EGFR expression has been shown to reduce risk of breast cancer in general (2,22).…”
mentioning
confidence: 99%
“…Previous studies have reported that PA-MSHA exhibits antitumor effect by the direct tumoricidal activity (Liu et al, 2009(Liu et al, , 2010 and also induces innate immune response against HIV in an infectious disease model (Hou et al, 2012). Here, to explore whether antitumor effect of PA-MSHA is also related to the induction of immune response, its therapeutic effect on lung cancer was investigated first.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first time that PA-MSHA has been shown to induce DC maturation in a TLR4-dependent manner to promote the activation and expansion of T cells and, further, to modulate the proliferation of T cells via TLR4 directly, which might lead to the effective inhibition of tumor growth. Previous studies mainly focused on the antitumor activities of PA-MSHA, such as the inhibition of the tumor cell cycle, the suppression of tumor cell proliferation, and the activation of apoptosisassociated pathways (Liu et al, 2010). Although several articles have described PA-MSHA as an adjuvant that could activate monocytes, macrophages, natural killer cells, and antigen-presenting cells to trigger innate immune response and even Th1-type immune response (Hou et al, 2012), none has ascribed PA-MSHA-mediated tumor inhibition to the immune cells or the immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation